African Football, Identity Politics and Global Media Narratives - Chari, Tendai. author. aut Link
XIV, 313 p.
Keywords: This edited volume addresses key debates around African football, identity construction, fan cultures, and both African and global media narratives. Using the 2010 FIFA World Cup in South Africa as a lens, it explores how football in Africa is intimately bound up with deeper social, cultural and political currents.